Electricity generation and petroleum hydrocarbon remediation in microbial fuel cell integrated with silver nanoparticles (AgNPs) from mangrove plant Melaleuca cajuputi - Tinchana, Sudarat; Rothjanawan, Kronsirinut; Meenapha, Ason; Chaijak, Pimprapa (Brawijaya University, 2026)
Petroleum hydrocarbon contamination is a critical global issue affecting both terrestrial and coastal soils. In this study, a soil microbial fuel cell (SMFC) integrated with silver nanoparticles (AgNPs) synthesized from Melaleuca cajuputi leaf extract was developed for simultaneous diesel remediation and bioelectricity generation. The diesel removal efficiency and electrochemical performance, including open-circuit voltage (OCV), current density (CD), and power density (PD) were evaluated. The results demonstrated that the SMFC system achieved a maximum OCV of 710.00 ± 10.00 mV, CD of 83.33 ± 0.35 A/m3 (3.50 ± 0.03 A/m2), and PD of 28.80 ± 0.10 W/m3 (1.15 ± 0.20 W/m2). In addition, a maximum diesel removal efficiency of 98.15 ± 0.15% was obtained. These findings suggest that the integration of AgNPs in SMFC systems is a promising approach for enhancing petroleum hydrocarbon remediation while generating sustainable energy.